Notes on Optimal Growth, Climate Change Calamities, Adaptation and Mitigation - Omar Chisari (Inter-American Development Bank (IDB), 2010)
A strategy of inclusion of adaptation and mitigation expenses in a model of optimal growth under threat of climate change calamities is discussed in these exploratory notes. Calamity is the result of a shock that reduces the utility level (even to extinction forever) and/or triggers a fundamental change of the economic structure. Mitigation expenses reduce the long-run probability of a calamity or the speed of convergence to it; adaptation expenses help to improve the standard of living after the calamity. The willingness to contribute to those expenses and the effects on the long-run capital stock of the economy depend on perceptions on how they will modify the law of evolution of probabilities of the shock and the standard of living after the shock. The choice between a clean technology and one that increases GHG emissions is also discussed.
Keywords: O44; 330; Climate Change; Growth; Adaptation; Mitigation